Public-Private Partnership in Water Supply of DKI Jakarta - Putri Permata Oktaviani; Entang Adhy Muhtar; Nina Karlina (Jurnal Manajemen Pelayanan Publik, 2020)
Drinking-Water Company (PAM) Jaya as a regional company is responsible for supply clean water in DKI Jakarta, is demanded to conduct partnerships with the private sector, namely PT Palyja and PT Aetra Air Jakarta. After the partnership, there are still many people who do not have access to clean water services. The purpose of this study is to find out and analyze the implementation of the Public-Private Partnership implemented by PAM Jaya and private partners in the supply of clean water in DKI Jakarta. The research method used qualitative research methods.  The theory used is the utilization of the Public-Private Partnership proposed by Emanual Savas (2000) which consists of roles and functions, competition, regulation, risk, procurement, and financing. The results of this study the implementation of the Public-Private Partnership in the supply of clean water in DKI Jakarta has not been effective because of the failure to fully utilize the Public-Private Partnership. The absence of competition and procurement processes between partners, the absence of regulations referred to so that the impact on the Cooperation Agreement (PKS) did not reflect public interests. There were roles and functions of PAM Jaya and private partners that were not conducted, unclear risk-sharing and compensation to private partners were more giving loss to the PAM Jaya, resulting in a shortfall. The author suggests that the PKS contract is needed, also the Provincial Government of DKI Jakarta needs to issue strict and clear regulations, improve services to the public, and no longer use the form of concession cooperation.